Dynamical analysis of stiffened plates under patch loading - Srivastava, A.K.L.; Pandey, S.R.; Kumar, Ashwini (Zielona Góra: Uniwersytet Zielonogórski)
The vibration characteristics of stiffened plates with cutouts subjected to in-plane partial edge loadings at one end at the plate boundaries are studied using the finite element method. Buckling loads and vibration frequencies are determined for different cutout ratios and extent of partial edge loading at one end. In the structural modelling, the plate and the stiffeners are treated as separate elements where the compatibility between these two types of elements is maintained. The main elegance of the formulation lies in the treatment of the stiffeners. The stiffeners can be placed anywhere within the plate element, and need not be placed on the nodal lines. The vibration characteristics are discussed and the results are compared with those available in the literature. Numerical results are presented for a range of cutout to plate size from 0 to 0.8.
Keywords: FEM; partial edge loadings; buckling load; vibration frequency; stiffeners